Leishmanial lipid suppresses the bacterial endotoxin‐induced inflammatory response with attenuation of tissue injury in sepsis. Issue 2 (2nd April 2014) - Chatterjee, Nabanita; Das, Subhadip; Bose, Dipayan; Banerjee, Somenath; Jha, Tarun; Saha, Krishna Das
Abstract : Leishmanial lipid as a strong protective agent against bacterial endotoxin‐induced inflammatory responses in vitro, and in murine systems toward organ injury. Abstract : The use of live, attenuated, or genetically modified microbes or their cellular component(s) or metabolites has begun to emerge as a potential new approach in medicinal research to deliver biologically active entities. Thus, advancing our knowledge of such microbe‐mediated therapy may suggest new avenues for therapeutic intervention in many diseases. We had earlier reported that the total lipid of attenuated Leishmania donovani suppressed the inflammatory responses in rheumatoid arthritis patients. Our present study reveals that the pLLD, isolated from pathogenic L. donovani, decreases the inflammatory level of bacterial endotoxin in stimulated mouse macrophages, as also in the in vivo murine system. It exerts the activity by reducing the level of different mediators, such as cytokine‐chemokine(s). It also suppresses the expression of the ubiquitous transcription factor NF‐κBp65 in stimulated macrophage cells, improves the endotoxin‐associated liver damage, reduces the vascular permeability factors, such as VEGF, and suppresses the expression of cell adhesion molecules, including ICAM‐1, VCAM‐1, PECAM‐1, P‐selectin, and E‐selectin, in liver of septic mice. These findings indicate that pLLD may prove to be a potential anti‐inflammatory agent and protect from endotoxin‐induced sepsis in hepatic impairment.